PENTINGNYA PELATIHAN KURIKULUM 2013 BAGI GURU - Sutjipto Sutjipto (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2016)
The purpose of this study is to express the importance of curriculum training for teachers before its implementation. Results of the study show, first, from the aspect of policy makers affirms that the naming of Curriculum 2013 curriculum ideas including competency standards and core competencies, and the basic framework and structure of the curriculum is essentially unchanged. Second, the curriculum changes and updates in curriculum 2013 includes the cohenrence of KI-KD (Core Competence â€“ Basic Competence) and adjustment of the document, structuring competence spiritual attitudes and social attitudes in all subjects, structuring competence which is not limited by deletion of taxonomic thinking processes, modification of learning and assessment, adjustment of the book contents towards the change of KI-KD and learning, and the provision of creative space for teachers in implementing the curriculum. Third, changes and updates in Curriculum 2013 that emphasizes on curriculum adjustment, easy to learn, easy to teach, measurable, and meaningful to learn is positively responded by those who implement the curriculum. Fourth, the implementation training of Curriculum 2013 is a strategic means to interpret the concept of change and updating of the curriculum as a whole. Fifth, the implementation training of Curriculum 2013 is a kind of art event to process various goals to harmonize the programmed policy by sharing ideas in order to lead to the ideal common understanding about the idea, design, and implementation of the curriculum.ABSTRAKÂ Tujuan dari penulisan artikel ini yaitu untuk mengungkapkan pentingnya pelatihan suatu kuri kulum bagi guru sebelum kurikul um i tu di impl ementasi kan. Hasil kajian menunjukkan, pertama, dari sisi pengambil kebijakan memberi penegasan bahwa penamaan kurikulum Kurikulum 2013; ide kurikulum yang mencakup standar kompetensi lulusan dan kompetensi inti, kerangka dasar dan struktur kurikulum hakikatnya tidak mengalami perubahan. Kedua, perubahan dan pemutakhiran Kurikulum 2013 mencakup koherensi KI-KD dan penyelarasan dokumen; penataan kompetensi sikap spiritual dan sikap sosial pada semua mata pelajaran; penataan kompetensi yang tidak dibatasi oleh pemenggalan taksonomi proses berpikir; penyelarasan pembelajaran dan penilaian; menyelaraskan isi buku terhadap perubahan KI-KD dan pembelajaran; dan pemberian ruang kreatif kepada guru dalam mengimplementasikan kurikulum. Ketiga, perubahan dan pemutakhiran Kurikulum 2013 yang mencirikan keselarasan, mudah dipelajari, mudah diajarkan, terukur, dan bermakna untuk dipelajari ditanggapi positif oleh pelaksana kurikulum. Keempat, program pelatihan pengimplementasian Kurikulum 2013 merupakan wahana yang strategis untuk memaknai konsep perubahan dan pemutakhiran kurikulum secara menyeluruh. Kelima, pelatihan pengimplementasian Kurikulum 2013 bagi guru merupakan perhelatan seni mengolah berbagai tujuan untuk menyelaraskan kebijakan yang diprogramkan melalui ajang berbagi guna mewujudkan pemahaman bersama yang ideal terhadap ide, rancangan, dan pengimplementasiannya.